Core Competence on Real Estate Industry in Globalization Phenomenon: A Contemporary Approach - Hastjarjo, Kelik; Yahya, Dwi Kartini; Afiff, Faisal; Rufaidah, Popy (International Journal of Economics and Financial Issues, 2016)
This article aims to review and integrate the strategic management and empirical literature on core competence, dynamic capabilities approach and real estate industry practices in order to pave the road for dissertation research. The article integrates the insights from strategic management perspective. Strategic management literatures and empirical studies are collected and reviewed. The findings from these studies are phenomenon and research problem, theorical foundations, literature map, the model and hypotheses to build core competence on real estate industry theory. The paper provides the new model for building core competence on real estate industry in globalisation phenomenon based on dynamic capabilities approach. It generates insights that may help firms to establish a strategic real estate development process and it may help to develop a more mature body of research on core competence. Keywords: Environment Risk, Dynamic Capability, Core Competence, Organizational Performance, Real Estate Industry JEL Classification: M